Dadih Susu Sapi Yang Dibuat Dalam Bambu Petung Bali Kering - I Made Sugitha; Ni Nyoman Puspawati (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2018)
Dadih is a typical Minang fermented milk made from buffalo milk , keep 2 nights in a bamboo tube covered with banana leaves. Microorganisms that play a role in this fermentation process comes from the inner surface of bamboo tube, the surface of banana leaves ( Sugitha, 1995). The process of making curd / fermented milk is still present in the area of West Sumatra while the potential of bamboo plants is almost there in Indonesia, including in Bali province. Bali is an area that has a lot of biodiversity of bamboo plants. In Bali there are various types of bamboo plants, one of which is bamboo petung. Traditionally, dadih was made by fermenting milk on bamboo and covered with banana leaves. The fermentation process naturally with lactic acid bacteria present in bamboo. The presence of lactic acid bacteria in bamboo will vary depending on the type of bamboo, the freshness and location of the growth. The research design used was experimental pattern with treatment: fresh bamboo petung (43.45% wc); half-dried bamboo petung (38.62% wc) and 25.77% wc dry bamboo petung). Through the parameters produced the characteristics of cow milk dadih made in dried bamboo petung contain: total BAL 5.6 x109 cfu / g; titratable acidity 48,42 mg / 100g; with a pH of 5.29